KAMPUNG WASUR SEBAGAI DESA SENTRA TEH CELUP SARANG SEMUT DI KABUPATEN MERAUKE - Candra Agus Wahyudhi; Supriyadi Supriyadi; Agus Kichi Hermansyah (Musamus University, 2021)
This community service activity program aims to make the community more independent in managing existing natural resources. In this activity, the community was provided with basic knowledge about making tea bags from ant nests to add to the economic value of these commodities. At the end of the activities, the community was also trained to carry out the product packaging process using the equipment provided. The methods used in this service activity are lectures and training on making tea bags and ending with packing tea bags into the packaging provided. This activity was held in the hall of the Bomi Sai Wasur building which was attended by around 30 participants from the Wasur village. The results of the activities were carried out in Wasur village by directly involving the local community show that the local community has a good understanding of the processing of natural resources around them. The community also gets good education about the use-value of a product that has a high selling value